The Legacy of Mies van der Rohe in Modern Movement and the Modern Architecture in Korea - Kimm, Jong Soung (Docomomo Journal, 2015)
The following article is an edited version of the keynote presented at the 13th International docomomo Conference that took place in Seoul, Korea, on September 2014. The paper discusses how “Western” architecture was first introduced to Korean soil: a French Catholic missionary-architect built the Seoul Cathedral at the end of the 19th century. American and Canadian architects built educational buildings for the Protestant missionary-founded colleges in Korea. Japanese civil servant architects built some public buildings during the colonial rule. The work of two prominent Korean architects, Kim Chung-Up and Kim Swoo-Geun are discussed. The author discusses his education at Mies van der Rohe’s Illinois Institute of Technology (IIT) in mid-1950s, his work for the Master during the 1960s, and his teaching at IIT 1966 and 1978. He describes how his dual position of teaching at IIT and working for Mies gave him the opportunity to work on three projects of importance: the Mies Retrospective in Berlin in 1968; the exhibition proposal for the extension of the Museum of Fine Arts in Houston of 1969; the Toronto-Dominion Bank executive floor and Banking Pavilion of 1966–1968. The author discusses several works of Mies van der Rohe to “demystify” the general perception that Mies was a rigid aesthetician: how Mies van der Rohe would arrive at design decisions not always sticking to the module, grid and geometry, contrary to the conventional reading of his architecture. The author then discusses five works from his three decades of practice with sac International in Seoul, highlighting where Mies’ influences might be found in these works: the Korea Military Academy Library of 1982; Seoul Hilton Hotel of 1983; the Weight-lifting Gymnasium for ‘88 Seoul Olympics of 1986; Kyongju Museum of Art of 1991; and the SK Group Office Building in Seoul of 1999. The paper also reflects on its relationship to the main theme of the recent International docomomo Conference in Seoul, Expansion and Conflict.